Calvinball: Users’ Rights, Public Choice Theory and Rules Mutable Games - Tarantino, Bob (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
This article proposes the “rules mutable game” as a metaphor for understanding the operation of copyright reform. Using the game of Calvinball (created by artist Bill Watterson in his long-running comic strip Calvin & Hobbes) as an illustrative device, and drawing on public choice theory’s account of how political change is effected by privileged interests, the article explores how the notion of a game in which players can modify the rules of the game while it is being played accounts for how users are often disadvantaged in copyright reform processes. The game metaphor also introduces a normative metric of fairness into the heart of the assessment of the copyright reform process from the standpoint of the user. The notion of a rules mutable game tells us something important about the kinds of stories we should be telling about copyright and copyright reform. The narrative power of the “fair play” norm embedded in the concept of the game can facilitate rhetoric which does not just doom users to dwell on their political losses, but empowers them to strategize for future victories.